Peran BUMDes Sektor Koperasi Pada Masa Pandemi Covid-19 Terhadap Kesejahteraan Petani Karet (Studi Pada Kampung Adi Jaya Kabupaten Way Kanan) - Novita, Eka; Nusantoro, Jawoto (Universitas Muhammadiyah Metro, 2022)
The objectives of this study are 1) to determine the effect of the role of BUMDes Jaya Abadi in the cooperative sector as a funding institution during the COVID-19 pandemic on the welfare of rubber farmers. 2) To determine the effect of the role of BUMDes Jaya Abadi in the cooperative sector in creating jobs during the COVID-19 pandemic on the welfare of rubber farmers. 3) To determine the effect of the role of BUMDes Jaya Abadi in the cooperative sector as part of public education during the COVID-19 pandemic on the welfare of rubber farmers. 4) To determine the effect of the role of BUMDes Jaya Abadi in the cooperative sector as a stabilizer during the covid-19 pandemic on the welfare of rubber farmers. 5) To find out the joint influence of the role of BUMDes Jaya Abadi in the cooperative sector as a funding institution, creating jobs, public education, and stabilizing during the COVID-19 pandemic on the welfare of rubber farmers. The population used in this study were rubber farmers in Kampung Adi Jaya, amounting to 125 people. The sample used in this study were 95 people. The data obtained were analyzed using multiple linear regression equations, coefficient of determination, t test, and f test. Based on the results of research and discussion, several conclusions can be drawn that funding institutions have a direct positive and significant influence on the welfare of rubber farmers. Creating jobs has a direct positive and significant impact on the welfare of rubber farmers. Public education has a direct positive and significant effect on the welfare of rubber farmers. Stabilizers have a direct positive and significant effect on the welfare of rubber farmers. Funding institutions, creating jobs, public education, and stabilizers together have a positive and significant influence on the welfare of rubber farmers. Keywords: welfare of rubber farmers, the role of cooperatives